Physiological and biochemical responses and hydration status in equines after two barrel racing courses - Gomes,Cláudio L.N. (2020)
ABSTRACT: Studies on biochemical constituents and hydration of horses in training or competitions are essential for the knowledge of their adaptive physiological and metabolic responses to the type of exercise inherent to the sport. The present research evaluated the effects of exercise on hydric status and physiologic and biochemical profiles in Quarter Horses during a barrel race training session. The design consisted of three evaluation times (T): at rest, before the start of physical activity (T0); immediately after a 10-minute warm-up trot and then running the barrel race courses twice with a 10-minute interval (T1); and after one hour’s rest after the second course (T2). The parameters analyzed were: heart rate (HR), respiratory rate (RR), body temperature (BT) and mucose color; the capillary refill time (CRT), packed cell volume (PCV), total plasma proteins (TPP), serum creatinine (CRE) and blood urea nitrogen (BUN) were evaluated and used to infer water status; plasma osmolarity (Osm) was measured; the electrolytes sodium (Na), potassium (K), chloride (Cl), total calcium (tCa), total magnesium (tMg) and phosphorus (P), plasma glucose (Glu) and lactate (Lac) and the muscle enzymes creattine kinase (CK) and aspartate aminotransferase (AST) completed the evaluated parameters. The data for the variables studied were submitted to ANOVA and the Tukey test at 5% probability. After exercise (in T1), HR, RR, BT, PCV, TPP, Glu, Lac, Cre increased (P<0.05), there was also increase in phosphorus and decrease in K (P<0.05), but there was no hypophosphatemia and hipokalemia, respectively. After rest (in T2), only glucose returned to baseline levels (T0) and, with lower mean values, HR, RR, BT, PCV, K and Lac did not return to baseline levels (T0), while P decreased (P<0.05). Osm, BUN, Na, Cl, tCa, tMg, CK and AST did not change between times (P>0.05). It was concluded that the maximum intensity exercise performed on two barrel race courses caused mild hemoconcentration, did not changed plasma osmolality or concentrations of important electrolytes and muscle enzymes of horses, but caused hyperlactatemia without the plasma lactate concentrations being fully recomposed after resting.